Computadores eletrônicos como agentes semióticos autônomos - Gazoni, Ricardo Maciel (2019)
The paper examines the concept of semiotic agency in light of the philosophy of Charles Sanders Peirce (1839-1914) and applies Peirce’s semiotics to the study of computers. It presents essential elements of Peirce’s philosophical framework, such as sign, interpretation, communication, and vagueness, as it is inherent in any natural language, before it focuses on the concepts of semiotic agency as well as Peirce’s broad concepts of mind and mental action. The author analyzes the electronic computer, an implementation of a universal Turing machine, one of the most versatile devices ever invented, which, early on, has raised conjectures as to the possibility of exhibiting intelligent behavior. The elements of Peirce’s philosophy introduced by the study are used in the analysis of the electronic computer to argue that it can be interpreted as a semiotic agent. A conceptual framework is proposed to introduce new ways of using the computer, particularly in programming in a dialogic process. The study addresses fundamental questions of computer science, computer philosophy, and artificial intelligence, aiming at a broader understanding of the limits of mathematical decidability and computability. Furthermore, it aims at extending the concept of autonomous semiotic agency to nonhuman agents, such as robots and autonomous automobiles. The results of this study are relevant to computer philosophy as well as to research on semiotic agency and intelligence in general